Ecological differentiation of calcareous vegetation across the lowlands and foothills of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question. What environmental parameters drive the differentiation of calcareous vegetation? Location. Calcareous rocks and outcrops in the lowland regions of Ukraine and adjacent foothill areas within 48.3–50.5 °N and 23.8– 38.2 °E. Methods. A database comprising 1704 phytosociological relevés of calcareous vegetation was compiled, of which 1512 were selected and classified using expert systems and the k-means method. Environmental differentiation was assessed based on geomorphological parameters and ecological indicator values ECODID. DCA ordination was applied to identify the parameters that significantly influence the structure of calcareous vegetation. In addition, univariate analyses of syntaxa distributions were performed, accompanied by boxplots to identify homogeneous groups and evaluate the significance of each environmental parameter. Nomenclature. Euro+Med PlantBase (https://europlusmed.org), Hodgetts et al. 2020, Index Fungorum (https://indexfungorum.org), Mucina et al. 2016, Didukh et al. 2018, Didukh et al. 2021, Vynokurov 2021. Results. Statistical analysis revealed that the primary environmental parameters determining the differentiation of calcareous vegetation are soil moisture and calcium carbonate content. These factors influence other key environmental characteristics, including soil acidity, total salt regime, and aeration. The vegetation communities, although strongly dependent on local microclimatic conditions, are also sensitive to regional macroclimatic factors. Additionally, elevation above sea level and slope steepness were found to affect environmental differentiation significantly. Conclusions. Calcareous vegetation is shaped by significant substrate heterogeneity and by the interactions among local and regional environmental drivers, resulting in pronounced environmental differentiation. The reliance on unique calcareous and gypsum substrates, together with specialised microhabitats, highlights the high vulnerability of these communities and underscores the need to prioritise their conservation.
Keywords: biodiversity, differentiation, environmental parameters, statistical analysis, vascular plants